Market multiples and stock returns among emerging and developed financial markets - Tahir Akhtar (Borsa İstanbul Review, 2021)
This paper compares the impact of market multiples on stock returns between emerging (ASEAN) and developed (European) financial markets. A t-test, fixed effects, and GMM are applied to a sample of 4725 firms for fifteen years. The findings show that market multiples differ across emerging and developed financial markets. In both markets, the ratios of price/book, price/cash flow, price/dividend, and price/sales positively affect stock returns. Price/earnings and dividend growth negatively affect stock returns in ASEAN. In contrast, price/earnings is insignificant, while dividend growth positively affects stock returns in European markets. The 2008-2009 financial crisis and the 2011-2012 European debt crisis have a negative impact on stock returns. Furthermore, the relationship between market multiples and stock returns differs significantly before and after the crisis. The study helps practitioners to understand that the characteristics of financial markets vary and so does the impact of market multiples on stock returns.
Keywords: G11; G12; 330; ASEAN; Europe; Market multiples; Panel data analysis; Stock returns